Legal Analysis of the Establishment of a New Autonomous Region of NTB Province into Sumbawa Island Province: Between Decentralization and Regional Challenges in NTB (Lex Journal : Kajian Hukum dan Keadilan, 2025)
The plan to divide West Nusa Tenggara Province (NTB) into two provinces, namely NTB Province and Sumbawa Island Province, has sparked debate in terms of constitutional law and decentralization policy. This study aims to analyze the legal basis for the formation of these new autonomous regions, while also examining the territorial challenges faced by NTB in the context of equitable development and public services. Using a normative and sociological approach, this study finds that constitutionally, the formation of Sumbawa Island Province is possible, but it must meet administrative, technical, and territorial requirements in accordance with laws and regulations. The main challenges lie in infrastructure inequality, human resource readiness, and local socio-political dynamics. Therefore, the decision to divide the province must take into account a thorough legal analysis and the real needs of the local community.